Factors related to first COVID-19 booster vaccine acceptance in Indonesia: A cross-sectional multi-center study - Mohi, Abdul R.; Kusuma, Ikhwan Y.; Massi, Muhammad N.; Bahar, Muhammad A. (Narra J, 2024)
A positive community perception of the coronavirus disease 2019 (COVID-19) vaccination program is crucial for increasing vaccination coverage and achieving herd immunity. This study aimed to identify factors influencing the acceptance of a COVID-19 booster vaccine in Indonesia. It was conducted as a cross-sectional, multicenter study using a validated questionnaire distributed online to Indonesian participants aged 18 years and older.  The questionnaire covered sociodemographic characteristics, clinical conditions of both the participants and their closest contacts, the Health Belief Model (HBM) domain, and preferences for the location of receiving a booster vaccine, as well as reasons for declining a booster vaccine. Of 1550 respondents, 78.6% had received the first COVID-19 booster dose. Sociodemographic factors influencing first booster vaccine acceptance in Indonesia included age (OR36–45 vs 18–25 years: 2.43; 95%CI: 1.13–5.24; OR>45 vs 18–25 years: 3.58, 95%CI: 1.96–6.52), length of education (OR13–16 vs <12 years: 1.34; 95%CI: 1.00–1.80; OR>16 vs <12 years: 4.15, 95%CI: 2.12–8.09), monthly income (ORIDR3,500,000 vs 1,500,000: 1.72; 95%CI: 1.19–2.49), and occupation (ORHealth workers vs not-working: 1.81; 95%CI: 1.00–3.29). Clinical aspects and HBM domains associated with booster vaccine acceptance were the presence of chronic disease (OR: 1.94; 95%CI: 1.03–3.66), previously tested positive for COVID-19 (OR: 1.90; 95%CI: 1.24–2.89), having a family member or friend who was hospitalized due to COVID-19 (OR: 1.86; 95%CI: 1.32–2.62), perceived susceptibility (OR: 1.20; 95%CI: 1.02–1.41), perceived access barriers to COVID-19 vaccination (OR: 0.52; 95%CI: 0.44–0.61), and perceived benefits of COVID-19 vaccination (OR: 1.67; 95%CI: 1.41–1.97). In conclusion, factors influencing the first COVID-19 booster vaccine acceptance in Indonesia ranged from demographic and clinical characteristics as well as HBM domains. Effective strategies to expand COVID-19 booster vaccine coverage should consider these factors to encourage participation in the vaccination program.